Pelaksanaan Vaksinasi Rabies pada Anjing dan Kucing Kecamatan X Koto Singkarang, Kabupaten Solok, Sumatera Barat - Mohammad Irham Bagus Santoso; Agus Setiyono (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Rabies vaccination has been carried out on dogs and cats in Nagari Tikalak, District X Koto Singkarak, Solok Regency, West Sumatra. Vaccination is held on Wednesday, July 17, 2019 in Tiga Jorong namely Jorong Pasir, Jorong Tengah, and Jorong Batu Api, Nagari Tikala. The purpose of vaccination is to prevent transmission of the rabies virus by rabies-transmitting animals. Rabies vaccination was carried out by one veterinarian, three FKH IPB students and four paramedics. Vaccination is done by going directly to the homes of residents who have dogs and cats. Implementation of rabies vasination has been carried out to prevent transmission of rabies to the community. Vaccination was carried out on 27 dogs and 13 cats. Keywords: cats, dogs, nagari tikalak, rabies vaccination